Metabolomic profiling of rectal microorganisms in Tibetan sheep across cold and warm seasons - An, Qi-Tala; Zhao, Zhipeng; Ren, Yaxiong; Liu, Xia; Yao, Liangwei; Chen, Siyuan; Yuan, Zhikuan; Feng, Peijian; Li, Wenhao; Du, Xiaohua (Frontiers in Veterinary Science, 2025)
The intestinal metabolites of Tibetan sheep play a vital role in the integrated regulation of the host and the microbe-gut-brain axis. The current study sought to investigate the characteristics of alterations in rectal metabolites and their functional implications during the cold and warm seasons in Tibetan sheep. A cohort of 12 ewes, approximately 1 week ± 1 month in age, exhibiting good body condition and a similar genetic background, was selected for metabolomic analysis of rectal contents collected during the warm season (August) and the cold season (December). The findings revealed significant differences in the rectal microbial metabolites of Tibetan sheep between the two seasons (P < 0.05), with a total of 476 differential metabolites identified in the positive ion mode (148 up-regulated and 328 down-regulated) and 383 differential metabolites in the negative ion mode (135 up-regulated and 248 down-regulated). These differential metabolites were mapped to 12 KEGG metabolic pathways (P < 0.05), including fatty acid biosynthesis, arachidonic acid metabolism, secondary bile acid biosynthesis, propionic acid metabolism, lysine degradation, and arginine and proline metabolism, which are linked to lipid metabolism, carbohydrate metabolism, and amino acid metabolism, respectively. The content of deoxycholic acid in the intestinal tract of Tibetan sheep was significantly higher during the cold season compared to the warm season (P < 0.05), while propionic acid was significantly lower (P < 0.05). These metabolites are involved in secondary bile acid biosynthesis and propanoate metabolism pathways. These results indicate significant seasonal variations in rectal microbial metabolites in Tibetan sheep. The identified metabolites may play a crucial role in regulating energy metabolism, inflammatory responses, and immune functions, thereby enhancing the adaptability of Tibetan sheep to the challenges posed by cold-season conditions.